The Emerging Role of Ofatumumab in the Treatment of Chronic Lymphocytic Leukemia - Nabhan, Chadi (Libertas Academica, 2011)
The treatment of chronic lymphocytic leukemia (CLL) has evolved over the past decade. Our better understanding of disease biology and risk stratification has allowed delivering more effective therapies. In fact, front-line chemoimmunotherapy has demonstrated improvement in overall survival when compared to chemotherapy in randomized studies. Yet, treatment of relapsed CLL remains challenging and few agents are effective in that setting. Ofatumumab (Ofa) is a humanized monoclonal antibody targeted against CD20 with demonstrable activity in rituximab-resistant CLL cell lines. This agent was recently approved for the treatment of relapsed/refractory CLL patients who have failed fludarabine and alemtuzumab. In this review, we provide a historical perspective on approaches to CLL as front-line and in the relapsed setting. We further summarize novel anti-CD20 antibodies with specific emphasis on ofa. We review studies that led to ofatumumab’s approval including pre-clinical data, trials using ofa in combination therapies, and adverse events/toxicities reported with this agent.